Human impacts on suspended sediment and turbidity in the River Murray, South Eastern Australia: Multiple lines of evidence. (5th February 2020) - Rutherfurd, Ian D.; Kenyon, Christine; Thoms, Martin; Grove, James; Turnbull, Jodie; Davies, Peter; Lawrence, Susan
Abstract: European settlement has led to increased loads of fine suspended sediment (SS) entering the River Murray, Australia's largest, and arguably, most important river. The River Murray's anthropogenic sediment history can be divided into four periods with varying source areas, sediment loads, and seasonal patterns. The Aboriginal period (before 1840) was characterized by clear water at summer low‐flows in the River Murray and its southern tributaries, with more sediment coming from the northern catchment than the southern, and the Darling River being turbid at all flows. There is little evidence that Aboriginal burning resulted in any measurable increase in SS. SS loads peaked in the 1870s and 1880s (the gold and gully period, 1850–1930) as valley floors were incised by gullies (mostly in northern tributaries), and gold sluicing flushed huge amounts of sludge into southern tributaries. Sedimentation in wetlands and on floodplains increased by 2–10 times in this period, and the biota in wetlands switched from clear water to turbid water communities. In the hiatus period (1930–1960) sediment supply from gullies and gold mining waned and low flow SS concentrations returned to low levels. Dam construction through the 1960s and 1970s (the regulation period, 1960 on) disconnected the River Murray from catchment derived sediment. Despite this, SS levels increased again: now largely derived from instream sources including bank erosion from long duration summer irrigation flows, the spread of bottom‐feeding carp ( Cyprinus carpio ), and wave erosion from boats. Erosion switched from winter to summer dominated. Significant investment in securing water for the environment in the Murray‐Darling Basin could be complemented by addressing in‐channel sediment sources in the River Murray itself to reduce turbidity. Overall, European era SS concentrations remain relatively low with small sediment delivery to the ocean (0.1 Mt per annum), despite high catchment erosion rates. This is due to poor sediment delivery efficiency through the low‐gradient landscape.